S-PkSec: an asymmetric key based security management scheme for sensor network operation - Haque, Md. Mokammel; Pathan, Al-Sakib Khan; Hong, Choong Seon (2008)
This paper proposes a public key based management scheme for secure sensor network operation namely S-PkSec (Public Key Based Security for Sensor Networks) and emphasizes detailed comparison with some similar type of schemes. Although there was a wide held belief of the incompatibility of public key cryptographic (PKC) schemes for wireless sensor networks (WSNs), some recent works have shown that, PKC or asymmetric key based schemes could be implemented for such networks in some ways. The major challenge of employing a PKC scheme in sensor network is posed by the limitations of resources of the tiny sensors. Considering this feature of the sensors, we enhance our previous work [1] with some effective comparisons and energy analysis with other two established asymmetric key based protocols. S-PkSec comprises basically of two parts; a key handshaking scheme based on simple linear operations and the derivation of decryption key by a receiver node. S-PkSec allows both base-station-to-node or node-to-base-station secure communications, and node-to-node secure communications. Analysis and simulation results show that, our proposed architecture ensures a good level of security for communications in the network and could effectively be implemented using the limited computation, memory and energy budgets of the current generation sensor nodes.